Econometric analysis of the determinants of adoption of alley farming by farmers in the forest zone of southwest Cameroon - Adesina, A.A.; Mbila, D.; Nkamleu, G.B.; Endamana, D. (Elsevier, 2000)
Slash-and-burn agriculture continues to expand in many parts of the forest zone of Cameroon. One alternative land use to slash-and-burn system is alley farming. This paper quantifies, using an econometric model, the factors determining farmers’ adoption and use of alley farming variants in southwest of Cameroon, based on a survey of 156 farmers in 11 villages in the region. The analysis showed that male farmers are more likely to adopt than women. Adoption is higher for farmers with contacts with extension agencies working on agroforestry technologies. Adoption is higher for farmers belonging to farmers’ groups. Adoption is lower for farmers in areas with very high population pressure, as farmers in such areas may have greater labor productivity from use of less labor intensive natural resource management technologies like chemical fertilizers. Adoption is higher for farmers in areas facing fuel wood scarcity. Farmers have made adaptations to the conventional alley farming technology recommended by researchers, the most significant adaptation being the introduction of fallow periods into the system. Farmers use alley farming as a land use option, not as a replacement for the slash-and-burn system, since land supply is still relatively elastic. Achieving increased impact with alley farming variants requires effective targeting. Results showed that econometric modeling using farmer and village characteristics, socioeconomic and institutional variables can lead to more effective targeting to farmers and locations where higher adoption rates may occur.